Chloe. 4, Rainy day - Tessier, Greg (Charmz, 2018)
As Valentine's Day approaches, Chloe is still sad over her breakup with her boyfriend. Then Chloe visits her grandmother at her seaside resort town and reunites with her childhood friend Mel who may not be so nice anymore.